1979
DOI: 10.1093/ajcp/72.6.1005
|View full text |Cite
|
Sign up to set email alerts
|

Pseudothrombocytopenia Due to Agglutinins

Abstract: Pseudothrombocytopenia may have any of a number of causes, one of which is agglutination in vitro. This phenomenon was found in samples of blood from six patients. A serum factor responsible for the agglutination was demonstrated. The factor was dependent upon the presence of EDTA and was more active at room temperature than at 37 C. It could be identified as an IgM immunoglobulin in four cases. In the other two cases definite characterization was not possible, but there was some evidence in favor of an IgM fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
28
0
1

Year Published

1982
1982
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 0 publications
1
28
0
1
Order By: Relevance
“…A spurious low platelet count due to platelet clumping or aggregation in EDTA-anticoagulated blood is an in vitro phenomenon known as EDTA-dependent pseudothrombocytopenia (EDTA-PTCP) (Gowland et al, 1969;Shreiner & Bell, 1973;Veenhoven et al, 1979;Onder et al, 1980). Recent studies have suggested that EDTA-PTCP is due to the presence of antiplatelet antibodies that recognize antigens on platelet membrane modified by EDTA (Mant et al, 1975;Robblee & Sherpro, 1976;Kunicki et al, 1981;Howard et al, 1982;Pegels et al, 1982;Ginsberg et al, 1986;van Vliet et al, 1986;Casonato et al, 1994;Bizzaro & Brandalisa, 1995).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A spurious low platelet count due to platelet clumping or aggregation in EDTA-anticoagulated blood is an in vitro phenomenon known as EDTA-dependent pseudothrombocytopenia (EDTA-PTCP) (Gowland et al, 1969;Shreiner & Bell, 1973;Veenhoven et al, 1979;Onder et al, 1980). Recent studies have suggested that EDTA-PTCP is due to the presence of antiplatelet antibodies that recognize antigens on platelet membrane modified by EDTA (Mant et al, 1975;Robblee & Sherpro, 1976;Kunicki et al, 1981;Howard et al, 1982;Pegels et al, 1982;Ginsberg et al, 1986;van Vliet et al, 1986;Casonato et al, 1994;Bizzaro & Brandalisa, 1995).…”
mentioning
confidence: 99%
“…EDTA-PTCP is of practical importance because the lack of recognition of this clinical entity may result in unnecessary treatment, such as steroid therapy or splenectomy, of patients with a normal platelet count (Berkman et al, 1991). Although EDTA-PTCP has been reported both in apparently normal individuals and in association with a variety of disease states such as malignancies, liver diseases, cardiovascular diseases, or autoimmune diseases (Gowland et al, 1969;Shreiner & Bell, 1973;Mant et al, 1975;Veenhoven et al, 1979;Onder et al, 1980;Berkman et al, 1991), there is no clinical evidence that associates the presence of EDTA-PTCP with specific diseases or the use of specific drugs. Therefore it is important to exclude the diagnosis of EDTA-PTCP in patients with a low platelet count in routine testing, and the development of a suitable method to evaluate the platelet counts in patients with EDTA-PTCP is of consequence.…”
mentioning
confidence: 99%
“…93 patients had antiplatelet antibodies (48 IgM, 30 IgG,3 IgA, and 12 had two different isotypes concomitantly). In 20% of patients, the presence of IgM antibodies characteristically accompanied platelet agglutination also at 37"C, and in citrated blood.…”
mentioning
confidence: 99%
“…It appeared to be an immunoglobulin molecule of unspecified class. A third type was recently described by Veenhoven et a1 [7], which shared features of both, in that it was not only EDTA dependent, but also most active at room temperature. In the six cases reported by these authors, the agglutinin was an IgM antiplatelet antibody.…”
Section: Introductionmentioning
confidence: 80%